The Influence of Parental Attention on the Mathematics Learning Outcomes of Class IV Elementary School Students - Peggi Khoirul Nadjiroh; Fikriana (Journal of Adaptive Education, 2025)
The main problem in this study was the low mathematics learning outcomes of the fourth grade elementary school students. The purpose of this study was to determine the effect of parental attention on the mathematics learning outcomes of the fourth grade elementary school students. This research used quantitative research with ex-post facto method. The population in this study was 218 students and the research sample was 73 students at SD Negeri Gugus Pattimura Tanjung Bintang. This study used a probability sampling technique, namely proportional random sampling. Data collection technique used was a questionnaire. Data analysis used a simple linear regression formula. The results showed that there was a significant influence of parents attention on mathematics learning outcomes with Fcount ≥ Ftable (19.194 ≥ 3.976). This means that the higher the attention given by parents to students, the higher the learning outcomes will be. Vice versa, if the attention given is low, the learning outcomes of students will also be low.